2020
DOI: 10.21203/rs.2.16366/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between nutrient intake, nutritional status and physical function of community-dwelling ethnically diverse older adults

Abstract: Abstract Background: There are limited longitudinal data regarding nutrient intake, nutritional status and physical function in community-dwelling ethnically diverse older adults. This study explored these variables and their relationship at baseline (n=100) and 8-months’ follow-up (n=81) among community-dwelling ethnically diverse older adults (≥60 years) in Birmingham, United Kingdom. Methods: Multiple-pass 24-hour dietary… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…From the effect of physical decline with age, there is a considerable amount of literature that demonstrates that the physical ability of an older adult has a direct impact on their nutritional status. For instance, a longitudinal study involving African migrants found that a decline in physical function over time worsened nutrient intakes and nutritional status of ethnic older minorities (73) . A good explanation for this relationship could be the difficulty in shopping and preparing food, especially traditional meals, due to physical limitations, which could eventually lead to inadequate dietary intake and malnutrition.…”
Section: Age and Ageingmentioning
confidence: 99%
“…From the effect of physical decline with age, there is a considerable amount of literature that demonstrates that the physical ability of an older adult has a direct impact on their nutritional status. For instance, a longitudinal study involving African migrants found that a decline in physical function over time worsened nutrient intakes and nutritional status of ethnic older minorities (73) . A good explanation for this relationship could be the difficulty in shopping and preparing food, especially traditional meals, due to physical limitations, which could eventually lead to inadequate dietary intake and malnutrition.…”
Section: Age and Ageingmentioning
confidence: 99%